Haptoglobin phenotypes and in vitro fertilization treatment outcomes. (October 2013) - Weiss, Amir; Ozeri, David; Beck-Fruchter, Ronit; Lavee, Michal; Geslevich, Yoel; Levy, Andrew P.
<x xml:space="preserve">Abstract</x> The haptoglobin (Hp) protein has been implicated in various aspects of reproduction. One possible mechanism is through its effect on angiogenesis. Angiogenesis plays a major role in follicle production. The Hp insertion polymorphism results in the production of Hp proteins denoted Hp 1-1, 2-1, and 2-2, with markedly different angiogenic activities. We sought to determine if the number of oocytes aspirated during in vitro fertilization is related to the Hp type and to compare clinical data and treatment outcomes. We conducted a prospective non-interventional study in an academic in vitro fertilization center serving northern Israel. All patients undergoing in vitro fertilization who agreed to have their haptoglobin phenotype and clinical data evaluated anonymously were included. The main outcome measure was the number of oocytes harvested from each aspiration. The groups did not differ regarding ethnicity or BMI, though women with the Hp1-1 phenotype had a longer duration of infertility (p = 0.037) and a higher gonadotropin requirement (p = 0.024) to achieve the same treatment outcome. Women with mechanical factor infertility were more likely (p = 0.042) to have the Hp 1-1/2-1 phenotypes than the Hp2-2 phenotype. There were no differences in the number of oocytes aspirated or the pregnancy rate. In summary, we could not establish a correlation between Hp phenotype and oocyte number or IVF outcomes though the Hp2-2 phenotype may be protective against mechanical factor infertility. Further studies with a larger sample size, particularly concerning the Hp1-1 phenotype, are required in order to extend these results.